Building the Nonuniversity, Tertiary Care Center Hepatobiliary and Pancreatic Surgery Practice: Structural and Financial Considerations. Issue 12 (December 2016) - Baker, Erin H.; Siddiqui, Imran; Vrochides, Dionisios; Iannitti, David A.; Martinie, John B.; Rorabaugh, Lauren; Jeyarajah, D. Rohan; Swan, Ryan Z.
Early in their careers, many new surgeons lack the background and experience to understand essential components needed to build a surgical practice. Surgical resident education is often devoid of specific instruction on the business of medicine and practice management. In particular, hepatobiliary and pancreatic (HPB) surgeons require many key components to build a successful practice secondary to significant interdisciplinary coordination and a scope of complex surgery, which spans challenging benign and malignant disease processes. In the following, we describe the required clinical and financial components for developing a successful HPB surgery practice in the nonuniversity tertiary care center. We discuss significant financial considerations for understanding community need and hospital investment, contract establishment, billing, and coding. We summarize the structural elements and key personnel necessary for establishing an effectual HPB surgical team. This article provides useful, essential information for a new HPB surgeon looking to establish a surgical practice. It also provides insight for health-care administrators as to the value an HPB surgeon can bring to a hospital or health-care system.